THE EFFECTIVENESS OF USING POWTOON AS MEDIA IN TEACHING VOCABULARY - Aspiani, Vidia; Finny Anita; Maliqul Hafis; Heti Susanti (Program Studi Pendidikan Bahasa Inggris, 2025)
The purpose of this research was to determine whether the use of Powtoon media is effective or not in teaching vocabulary and to assessthe effect of the Powtoon media in teaching vocabulary to grade VIII A students of SMPN 1 Kendawangan. This study uses a quantitative method, specifically a pre-experimental design with a one-group pre-test post-test. The subjects in this study were 24 eighth-grade A students at SMPN 1 Kendawangan. In this study. the measurement technique was used to collect data through tests. Pre-test and post-test assessments were given to collect data from students. The collected data analysis using descriptive statistics with SPSS for Windows version 24. The paired sample test analysis was used to test the hypothesis. In addition, Cohen's effect size was used to evaluate the impact of using the PowtoonMedia in teaching vocabulary.The research findings of the study showed the effectiviness of the Powtoonmedia in teaching vocabulary to eighth grade students of SMPN 1 Kendawangan. This was evidenced by the differences observed in the mean scores between the pre-test (48.75) and post-test (72.70), indicating a positive change after the treatment. The standard deviation pre-test (8.75) and the post-test (7.79). Furthermore, the sample t-test of 17.380 and the degrees of freedom (df) 23. This result allows us to reject the null hypothesis (Ho) and accept the alternative hypothesis (Ha). In conclusion, PowToon media is effective in teaching vocabulary. The effect size. based on the Cohen effect, was determined to be 1.44, indicating a strong effect of the Powtoon media in teaching vocabulary.